(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To explore the social media-related stress levels and to analyze the associated factors among first-year medical students at Phenikaa University. Methods: The cross-sectional study included 219 first-year students enrolled in a six-year program in Medicine, Dentistry, or Traditional Medicine at Phenikaa University, Hanoi, Vietnam. A structured questionnaire was used, covering three domains: socio-demographic information, health risk behaviors, and social media-related stress. Univariate and multivariate linear regression analyses were conducted to explore the associations between social media-related stress scores and covariates. Results: The median stress score was 8 (interquartile range [IQR]: 4–12) for social media neglect and 12 (IQR: 6–13) for negative reactions on social media. Students who smoked had significantly higher scores of stress related to neglect (by 4.5 points) and stress related to negative reactions (by 4.7 points) compared to non-smoking students. Additionally, students who used social media for more than two hours before sleep reported higher stress scores, while those who studied for at least two hours per day had significantly lower stress scores from neglect Conclusions: Stress related to social media neglect and negative reactions was more prevalent among first-year medical students at Phenikaa University who smoked or spent over two hours on social media before bedtime. Conversely, students who dedicated more time to self-study experienced lower levels of stress from neglect. These findings highlight the importance of promoting healthier lifestyle choices and academic habits among first-year medical students.